Aspectos valorativos do cerrado goiano como provedor das plantas medicinais para fins de uso tradicional: o caso do Grupo Espírita da Paz - Sena, Carlos Eduardo Silva (2018)
Medicinal herbs are important natural riches to several cultures, mostly because of their phytotherapic use originated from traditional knoledge aqcired through direct contact with nature. Given that relevance, to secure products’ quality and to boost the sector’s progress, a group of institutions developed themselves attending to the Política Nacional de Plantas Medicinais e Fitoterápicos (PNPMF), however, contradictorily, they stablish barriers to the production chain base constituted by strategic agents to the sector’s consolidation in Brazil. Besides, added to these barriers, when it comes to brazilian biomes, specially Cerrado, despite it’s composition by an abundant floristic diversity, that biome faces a scenario of land occupation due to agriculture advent, what sugests that services of medicinal herbs provision might be threatened. Therefore, this work highlights the value of the phytotherapy performed by Grupo Espírita da Paz as a critical point of sucsess on developing medicinal herbs production chain from income generation, cultural recognition and conservation of biomes that provide genetical resourses to phytotherapic herbs production, proposing a strategic guideline to the institutional improvement of the sector from this perspective.